LIMITATIONS ON STOCK DIVIDENDS. - Kerrigan, Harry D. (The Accounting Review, 1937)
Abstract Since stock dividends do not distribute corporate assets or affect the safety of creditors, legal restrictions on their declaration may be deemed less necessary than in the case of cash dividends. Yet a closer study discloses a real need for imposing limitations on stock dividends. Restrictions on stock dividends must of course be expected to be different from those applied against cash dividends, because of the different problems raised by the two types. Stock dividends involve the issuance of new shares, calling for the increase of capital stock and reduction of the surplus or profits from which they are declared. Stock dividends also result in a form of recapitalization. Where there is more than one class of stock outstanding, the realignment of net worth accounts may affect the participation rights of a particular class of stockholders in assets, in earnings, and in management. It is the purpose of the present paper to snmmarize the more important limitations on stock dividends under the existing American law as found in the statutes and decisions and to raise questions, where the occasion appears, concerning the efficacy of these systems of control from the standpoint of the public interest.